Analisis Faktor-Faktor Yang Mempengaruhi Wajib Pajak Mengenai Penggelapan Pajak (Tax Evasion) - Muhammad Ridwan; Ajat Sudrajat (Institut Ilmu Sosial dan Manajemen STIAMI, 2022)
Tax is one of the main sources of state revenue and expenditure. The phenomenon is that there are still some taxpayers who try to reduce the amount of tax owed by tax evasion, which is an effort to relieve taxes by violating the law. Meanwhile, this study aims to analyze factors such as the tax system, justice, and discrimination against taxpayers regarding tax evasion. The data obtained comes from questionnaires filled out by 100 individual taxpayers at KPP Pratama Jakarta Pasar Rebo. This study uses a quantitative approach with accidental sampling, the data analysis techniques carried out consist of descriptive statistics, data quality tests, classical assumption tests, hypothesis testing, and multiple linear regression model analysis. The results of this study indicate that the taxation system has a significant effect on tax evasion, this is evidenced by a significance value of 0.021<0.05, while justice and discrimination have no significant effect on tax evasion. This is evidenced by the significance value of justice of 0.082>0.05 and the significance value of discrimination of 0.068>0.05. Simultaneously the taxation system, justice, and discrimination have an effect of 36.1% on tax evasion. While the remaining 63.9% is explained by other variables not examined in this study.